PENGARUH PENGETAHUAN DAN MINAT BERTRANSAKSI MENGGUNAKAN LAYANAN QRIS DENGAN TECHNOLOGY ACCEPTANCE MODEL (TAM) SEBAGAI VARIABEL MEDIASI - Engko, Cecilia; Limba, Franco Benony; Achmad, Alda Puspita (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the influence of the technology acceptance model (TAM) as a mediating variable in the relationship between knowledge and interest in transactions using the Indonesian Standard Quick Response (QRIS) service. This research is a quantitative study using primary data obtained from distributing questionnaires. The population in this study are MSME coffee shop entrepreneurs who use QRIS. The sampling technique used the Saturated Sampling technique with a total of 43 UMKM Coffee shop business actors as respondents. The test tool used is SmartPLS 3 with the PLS-SEM (Partial Least Square-Structural Equation Modeling) analysis method. The results of this study are 3 hypotheses proposed, two of which can be accepted and one hypothesis is rejected. The accepted hypothesis is the influence of knowledge on intention to use through perceived usefulness and the effect of knowledge on intention to use through perceived ease of use. Meanwhile, the hypothesis that was rejected was that knowledge had a direct effect on interest in using QRIS